Empathic Robots for Long-term Interaction - Leite Iolanda; Castellano Ginevra; Pereira, André; Martinho, Carlos; Paiva, Ana (International journal of social robotics, 2014)
As a great number of robotic products are entering people’s lives, the question of how can they behave in order to sustain long-term interactions with users becomes increasingly more relevant. In this paper, we present an empathic model for social robots that aim to interact with children for extended periods of time. The application of this model to a scenario where a social robot plays chess with children is described. To evaluate the proposed model, we conducted a long-term study in an elementary school and measured children’s perception of social presence, engagement and social support.